Monazite U-Pb age, geochemistry, and genesis of ore-bearing granites in the Zhukeng tungsten deposit, southern Jiangxi Province - GAO Yuan; WANG Ying; WANG Hai; XU Zhe; ZHANG Yong; ZHOU Yu; ZHANG Fangrong; SUN Chao; HE Bin; ZHANG Siyuan; ZHANG Fushen (Dizhi lixue xuebao)
Objective  The composite Zhukeng granite is composed of two-mica granite and muscovite granite and closely related to tungsten and niobium-tantalum deposits in southern Jiangxi Province.   Methods  Based on systematic lithogeochemical analysis and rock-forming age determination of muscovite granite and two-mica granite from the Zhukeng tungsten deposit, combined with regional studies concerning diagenesis and mineralization, the genesis and tectonic setting of the rock mass are discussed.   Result  The LA-ICP-MS analysis of monazite from the fine-grained muscovite granite yielded a 206Pb/238U weighted average U-Pb age of 156.7 ± 1.3 Ma. Major elements exhibit high silica contents (SiO2 ranging from 65.54% to 74.95%), high alkalis contents (Na2O+K2O ranging from 8.48% to 12.85%), high aluminum contents (A/CNK ratios ranging from1.10 to 1.22), and low magnesium contents. The total rare earth elements (ΣREE) range from 61.12×10−6 to 173.98×10−6, and there are right-dipping light rare earth enrichment patterns with a weak negative Eu anomalies. The trace elements Rb, Ta, Th, Pb, Nd, and Hf are enriched, while Ba, Nb, Sr, and Ti are depleted, indicating a highly differentiated S-type granite. The LA-ICP-MS analysis of monazite U-Pb from the two-mica granite yielded an 206Pb/238U weighted average age of 159.5 ± 0.5 Ma. Major elements exhibit high silica contents (SiO2 ranging from 75.02% to 77.03%), high alkalis contents (Na2O+K2O ranging from 5.92% to 8.58%), high aluminum contents (A/CNK ranging from 1.14 to 1.65), and low magnesium contents. Total rare earth elements (ΣREE) range from 106.86×10−6 to 124.24×10−6, and there are right-dipping light rare earth enrichment patterns with a significant negative Eu anomalies. The trace elements Rb, Ta, Th, Pb, Nd, and Hf are enriched, while Ba, Nb, Sr, and Ti are depleted, suggesting a highly differentiated S-type granite.   Conclusion  By combining geochronological and lithogeochemical characteristics, the authors conclude that the Zhukeng tungsten deposit formed during an Upper Jurassic mineralization event caused by large-scale granitic magmatic activity related to subduction.